Malignant fibrous histiocytoma in a budgerigar (Melopsittacus undulatus) - ÖZEN Η.; DAĞ, S.; KARAKURT, E.; BÜYÜK, E. (Journal of the Hellenic Veterinary Medical Society, 2020)
In this report, a case of malignant fibrous histiocytoma in a budgerigar (Melopsittacus undulatus) is described. At necropsy, a tumorous subcutaneous mass was noted to be located under the right wing at the level of humerus in a budgerigar. On microscopic examination, the tumor was composed of pleomorphic cells having mostly round to oval large nucleus. Presence of occasional bands composed of fibroblastoid cells were noted. Occasional giant cells and mitotic figures were also observed. Based on the microscopic findings, a diagnosis of malignant fibrous histiocytoma was made. The present case in an exotic bird was found to be interesting, since malignant fibrous histiocytomas are rare tumors of domestic animals and mostly seen in dogs.